PENGEMBANGAN PEMBELAJARAN MATEMATIKA BERDASARKAN KURIKULUM MERDEKA BAGI GURU-GURU SD NEGERI 1 KAIRATU KABUPATEN SERAM BAGIAN BARAT - Huwaa, Novalin Calasin; Ratumanan, Tanwey Gerson; Silitonga, R H Yanti; Kempa, Vicardy (Universitas Pattimura, 2023)
This community service activity aims to help teachers in SD Negeri 1 Kairatu, Seram Bagian Barat district, develop a flow of learning objectives and teaching modules, and implement differentiated learning based on the independent learning curriculum. This activity was carried out in the form of socialization. To determine the results, participants were given a questionnaire containing questions related to the material provided before and after the socialization activity. The questionnaire results showed that 10 participants (100%) already understood how to compile the flow of learning objectives and teaching modules and were able to apply differentiated learning to their learning